2016
DOI: 10.1007/s10342-016-0946-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between height growth and molecular genetic variation in Douglas-fir (Pseudotsuga menziesii) provenances

Abstract: Douglas-fir (Pseudotsuga menziesii) is a conifer tree native to western North America. In central Europe, it shows superior growth performance and is considered a suitable substitute for tree species impaired in vitality due to climate change. Maintenance and improvement of growth performance in a changing environment is a main challenge for forest tree breeders. In this context, genetic variation as a factor underlying phenotypic variation, but also as the basis for future adaptation, is of particular interes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…The origins differ in elevation (AR: 650 m, LA: 210 m), mean annual temperature (AR: 7.8 °C, LA: 10 °C) and most importantly in mean annual precipitation (AR: 500 mm, LA: 1475 mm). Recent studies using SNP [ 77 ] and microsatellite markers [ 78 ] revealed a clear genetic differentiation of these two provenances. For this study we used 50-year-old Dougls-fir trees from two common garden experiments near Schluchsee (S; 47°84′ N, 8°11′ E) and Wiesloch (W; 49°30′ N, 5°53′ E) in south-western Germany.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origins differ in elevation (AR: 650 m, LA: 210 m), mean annual temperature (AR: 7.8 °C, LA: 10 °C) and most importantly in mean annual precipitation (AR: 500 mm, LA: 1475 mm). Recent studies using SNP [ 77 ] and microsatellite markers [ 78 ] revealed a clear genetic differentiation of these two provenances. For this study we used 50-year-old Dougls-fir trees from two common garden experiments near Schluchsee (S; 47°84′ N, 8°11′ E) and Wiesloch (W; 49°30′ N, 5°53′ E) in south-western Germany.…”
Section: Methodsmentioning
confidence: 99%
“…The two sites differ in annual precipitation (S: 1345 mm, W: 660 mm) as well as in elevation (S: 1050 m, W: 105 m above sea level) and annual mean temperature (S: 6.1 °C, W: 9.9 °C). A detailed description of the provenances and the two field sites can be found in [ 78 , 80 ]. At each field site needle samples were taken repeatedly from 8 trees per provenance and on four different dates during the 2010 growing season (in Schluchsee on May 27, June 30, July 28, September 15; in Wiesloch on May 12, June 16, July 14, September 8; these eight sampling dates reflect the levels of the factor DATE that was used for modeling of gene expression, see below).…”
Section: Methodsmentioning
confidence: 99%
“…Provenances from coastal British Columbia, the Western Cascade Mountains and Oregon with a mean annual temperature ranging from 6 to 9.5°C are predicted to be the most productive for Central Europe under both current and future climate conditions (Chakraborty et al 2016). They are also characterized by the highest genetic diversity for the Douglas-fir (Table S1, Figure S1 in the supplementary materials), with a peak in Northern Oregon and Southern Washington west of the Cascades and decreasing trends towards south and north of the distribution range (Li and Adams 1989;Neophytou et al 2016;van Loo et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Growth changes among seedling families and/or clones have been largely observed in coniferous and broad-leaved species [17,34,35]. Similarly, Chinese fir species have expressed a greater range of heritable variations between families or provenances [3], resulting in larger differences in their growth and nutrient use efficiency [7,36].…”
Section: Discussionmentioning
confidence: 99%